2016
DOI: 10.1016/j.rvsc.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protective immune response against fowl typhoid in chickens vaccinated with the attenuated strain Salmonella Gallinarum Δ cob SΔ cbi A

Abstract: Salmonella enterica serovar Gallinarum biovar Gallinarum (SG) causes fowl typhoid in chickens, a septicemic infection which results in high mortality rates. This disease causes high economic impact to the poultry industry worldwide because of the mortality or elimination of positive flocks to control bacterial dissemination. Live vaccines are used in the fields, however the characterization of immune mechanisms important for protection are being studied to improve the efficacy of vaccination schemes. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…To promote the effective reproduction and growth of chickens and their global trade, attempts have been made to vaccinate chickens with live-attenuated strains of S . Gallinarum to control fowl typhoid (Kwon and Cho, 2011 ; Penha Filho et al, 2016 ; Wigley, 2017 ). However, live-attenuated vaccines retain some virulence and the protective effects of the vaccines are not yet completely satisfactory (Penha Filho et al, 2010 ; Ji et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To promote the effective reproduction and growth of chickens and their global trade, attempts have been made to vaccinate chickens with live-attenuated strains of S . Gallinarum to control fowl typhoid (Kwon and Cho, 2011 ; Penha Filho et al, 2016 ; Wigley, 2017 ). However, live-attenuated vaccines retain some virulence and the protective effects of the vaccines are not yet completely satisfactory (Penha Filho et al, 2010 ; Ji et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivated and/or live attenuated vaccines are used to prevent poultry infection with Salmonella organisms through promoting acquired immunity [6]. Salmonella vaccination has been proven to have some advantages that include reduction of transmission rate, either horizontal or vertical, of Salmonella among broiler breeder and/or broiler chicks [7], lowering the prevalence rate of contaminated table eggs with this pathogen [8] and improving survival rate [9]. Nevertheless, Berghaus et al [10] reported that this measure cannot decrease the environmental contamination of a breeder farm with Salmonella.…”
Section: Introductionmentioning
confidence: 99%
“…Enteritidis vaccine strain, JOL919, induced significant systemic immunoglobulin responses in chickens after inoculation ( 22 ). Another study reported that IgG levels were significantly higher in chickens vaccinated with the cobS and cbiA mutant S. Gallinarum strains than in the control group ( 23 ). Similarly, in this study, all chickens immunized with 5 × 10 6 and 5 × 10 7 CFU of Z11Δ rfbG had significantly higher levels of S .…”
Section: Discussionmentioning
confidence: 99%